PENGARUH HAFALAN JUZ AMMA DAN SEMAAN AL QURAN TERHADAP MORAL SISWA DI SDN JAGALAN KOTA MOJOKERTO - Barokatul Fatimah; Atim S; Muhtadi (FAI- Undar, 2021)
Nowadays, memorizing Juz Amma and reading Al Qu’an’s activities are needed to be held to increase the improvement of student’s morality. Problem of this research is influence of memorizing Juz Amma and reading Al Qur’an to students’ morality. Objectives of this research is to know there is influence or not between memorizing Juz Amma and reading Al-Qur’an to students’ morality in SDN Jagalan Mojokerto City. Population of this research is 57 students of IV, V, and VI grade in SDN Jagalan Mojokerto City. Analysis methods that used in this research are Pearson Correlation test (product moment), coefficient determination (adjusted r square), and hypotheses test (t test and F test). Result of hypotheses test (t test), memorizing Juz Amma has significant valueat the amount of 0,000 < α (0,05) and reading Al Qur’an 0,025 <α (0,05). Based on hypotheses test (F test) has significant value at the amonut of 0,000 <α (0,05), so can be concluded that partially and simultanously memorizing Juz Amma and reading Al Qur’an both of them has significant influence to student’s morality.